Evaluasi Perlakuan Akuntansi terhadap Selisih Kurs pada Perusahaan Tepung Kelapa di Sulawesi Utara - Sengkey, Marthen (JBE (Journal of Business and Economics); Volume 2 No.1, 2003 JBE UNKLAB, 2003)
A coconut Flour company is an oriented international market company with foreign currency transaction. Both export and import transaction connect with the foreign currency, and now the actual problem is about the exchange rate. This situation has made difficulty for the accounting acceptance. The accounting acceptance for the exchange rate must be fit and proper to the Income Statement information which influence to the exchange rate fluctuation. The purpose of this research is to know how accounting acceptance to exchange rate in those company and to compare accountancy acceptance to exchange rate to reconsider PSAK No. 10. The analysis method which has use is descriptive analysis method. The method is compare the data with theory and to discuss to get the result and suggestion as an input for company. The research show the accounting acceptance to exchange rate for those company not suitable to PSAK No. 10. United Coconut Tina Company applied accounting acceptance using approximately rate for 1 (one) month. Tropica Coco Prima and Setia Tri Jujur Bersama Companies have not used PSAK No. 10, so the Income Statement not show the real gain or losses.